PENERAPAN ANALYTICAL HIERARCHY PROCESS DALAM WEBSITE PEMILIHAN SMARTPHONE XIAOMI - Kuwat Setiyanto; Dimas Rizki Dwiyanto (Jurnal Teknik dan Science, 2023)
A smartphone is a communication tool that has a multitude of features such as communicating, playing games, photography and so on, this tool has become one of human needs in this digital era. Because of this, many people want to have their dream smartphone. But day by day there are more and more variations, especially many brands competing to be the cheapest with complete features, one of which is the Xiaomi brand. This makes potential buyers confused about choosing a smartphone that suits their needs. A Website-based Decision Support System in Smartphone Selection using the Analytical Hierarchy Process method was created to help find a cellphone that suits the buyer's wishes. In order to choose the right recommendation according to smartphone criteria that suits the buyer's needs,